Penguatan Manajemen dan Strategi Pengelolaan Kolam Renang BUMDes Tirta Arum untuk Peningkatan Pendapatan Desa - Dewi Yuniar Magetana; Dina Amalia Mahmudah; Danang Satrio; Supajar Bayu Aji; Kalina Faradisa Widodo; Fathia Zulfa; Nadia Chusna Chotimah; Farah Ulayya (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The objective of this mentoring activity is to increase the capacity of swimming pool managers, particularly in strengthening management and sustainable management strategies. With this increased capacity, it is hoped that Tirta Arum Swimming Pool can develop into a valuable village asset, both economically and socially. The swimming pool will not only provide a source of income for the village but also serve as a means of recreation, education, and social interaction for the surrounding community. The method used in this mentoring activity is Participatory Rural Appraisal (PRA), an approach that emphasizes active community participation in every stage of the planning process, decision-making, and program implementation. PRA enables village communities, including Tirta Arum Village-Owned Enterprise (BUMDes) managers, to analyze their environmental conditions, identify problems, and design contextual and sustainable solutions. This approach is implemented through structured mentoring, education, and training activities. Direct community involvement aims to foster a sense of ownership and responsibility for swimming pool management. In addition, with training tailored to local needs, managers are expected to be able to apply effective management principles, from planning and financial management to customer service and promotional strategies. Thus, the results of this activity are not only temporary improvements, but also long-term empowerment that contributes to the independence and business aspirations of the Village-Owned Enterprise (BUMDes). Through the PRA method, this activity not only provides an immediate solution to swimming pool management problems but also increases the independence of the community and managers in developing and operating the business sustainably. This increased community participation is expected to foster a sense of ownership (a sense of belonging) towards the swimming pool as a shared property.